Investigation of oil-water flow in concentric and fully eccentric annuli pipes. (November 2019) - Ibarra, Roberto; Nossen, Jan
Highlights: Oil-water flows in concentric and fully eccentric annuli were investigated. Flow regimes in concentric annulus exhibit a higher level of mixing. Mean water holdup is higher in fully eccentric annulus for a given flow condition. Frictional pressure gradient in concentric annulus is higher than in fully eccentric. A viscosity model was modified to account for the level of dispersion as function of the flow velocity. Abstract: Experimental investigations are performed on co-current flow of oil (Exxsol D60) and water in concentric and fully eccentric annuli with the inner pipe located at bottom of the outer pipe. The annulus outer and inner pipe have an inside diameter of 99 mm and outside diameter of 50 mm, respectively. This yields a diameter ratio of K  = 0.505. The flow conditions studied span mixture velocities and input water cuts in the range 0.50–1.75 m/s and 10–90%, respectively, at pipe inclinations of 0° and 4° upward. Flow regimes have been identified and maps constructed using instantaneous images of the flow from high-speed cameras (shadowgraph) and X-ray chordal holdup measurements along the vertical projection. Flow regimes in the concentric annulus exhibit a higher level of mixing than that observed in the fully eccentric configuration. The transition to dispersed flow occurs at lower mixture velocities in the concentric annulus. Measurements from broad-beam gamma densitometers reveal that the mean water holdup is higher in the fully eccentric annulus for a given mixture velocity and input water cut. The higher water accumulation in this annulus configuration can be attributed to a low velocity region in the narrow gap at the annulus pipe bottom. The frictional pressure gradient in the concentric annulus is higher as compared with the fully eccentric configuration. Peaks in the pressure gradient profile, for a constant mixture velocity, are observed at high water cuts ( i.e. WC ≥ 50%) at the transition between dual continuous and dispersed flows. Pressure gradient data are compared with predictions using the homogeneous and two-fluid model. In general, the homogeneous model using a modified Brinkman (Brinkman, 1952)/Roscoe (Roscoe, 1952) dispersion viscosity model shows the best agreement with data in both concentric and fully eccentric annuli.